Hexagonal boron nitride powder and method for producing the same, cosmetic and method for producing the same, and quality evaluation method
Patent Information
- Application Number
- CN202180099421.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-06-16
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2041-06-16
AI Technical Summary
[0029]本公开的一个方式可提供一种六方晶氮化硼粉末及其制造方法,其可制造出延展性优异的化妆品。另外,通过使用上述六方晶氮化硼粉末,可提供延展性优异的化妆品及其制造方法。
Smart Images

Figure CN117500751B_ABST
Abstract
Description
Technical Field
[0001] This disclosure relates to a hexagonal boron nitride powder and its manufacturing method, cosmetics and their manufacturing methods, and quality evaluation methods. Background Technology
[0002] Boron nitride has lubricating properties, high thermal conductivity, and insulation properties, and is used in a wide range of applications, including solid lubricants, mold release agents, fillers for resins and rubbers, raw materials for cosmetics, and heat-resistant insulating sintered bodies.
[0003] As a component of cosmetics, hexagonal boron nitride powder can improve smoothness, spreadability, opacity, and gloss. In particular, hexagonal boron nitride powder exhibits superior smoothness compared to talc and mica powders, which have similar functions, and is therefore widely used in cosmetics requiring excellent smoothness. Patent Document 1 proposes setting the ratio of shear stress to applied pressure within a specified range to improve smoothness.
[0004] Existing technical documents
[0005] Patent documents
[0006] Patent Document 1: Japanese Patent Application Publication No. 2019-43792 Summary of the Invention
[0007] To meet the increasing demands of customers for cosmetics, the properties of the raw materials used in cosmetics also need to be further improved. Therefore, raw materials used in products such as foundation are considered to have superior spreadability. On the other hand, hexagonal boron nitride powder is prone to forming agglomerates, which is believed to affect spreadability. Therefore, this disclosure provides a hexagonal boron nitride powder capable of producing cosmetics with excellent spreadability, and a method for manufacturing the same. Furthermore, this disclosure provides a cosmetic with excellent spreadability and a method for manufacturing the same by using the aforementioned hexagonal boron nitride powder. Additionally, this disclosure provides a quality evaluation method that can easily evaluate the quality of hexagonal boron nitride powder or powder compositions containing it.
[0008] [Problem-solving methods]
[0009] One aspect of this disclosure involves a hexagonal boron nitride powder with an oxygen content relative to the specific surface area (N) obtained by nitrogen adsorption of 0.1 g / 100 m³. 2The following describes the characteristics of hexagonal boron nitride powder. This hexagonal boron nitride powder has a low oxygen content per unit surface area. Therefore, for example, in an atmospheric environment, moisture is difficult to adsorb onto the surface of the hexagonal boron nitride particles. It also reduces surface static electricity. It is speculated that for these reasons, the aggregation of the hexagonal boron nitride powder is suppressed, resulting in a powder with excellent ductility. This hexagonal boron nitride powder is suitable for use as a raw material in cosmetics.
[0010] In another aspect of this disclosure, the hexagonal boron nitride powder, in the inclined rolling ball adhesion test with an inclined plate having an inclination angle of 30 degrees as specified in JIS Z 0237:2009, when applied to the bonding surface with ball number 7 using a coating plate at a speed of 1 cm / s from one end of the bonding surface to the other, achieves a coating area ratio of 77% or more. Here, the aforementioned coating area ratio is the ratio of the coating area to the total area of the central region of the bonding surface when 0.1 g of hexagonal boron nitride powder is applied to the bonding surface. The central region is a square area with a side length of 10 mm, located 10 mm away from one end of the bonding surface. The entire hexagonal boron nitride powder is disposed on one end of the bonding surface, between imaginary extensions of a set of opposite sides that define the central region and follow the direction of application of the hexagonal boron nitride powder.
[0011] The aforementioned hexagonal boron nitride powder exhibits a high coating area ratio on the bonding surface, resulting in excellent spreadability and fineness. Furthermore, the performance of the hexagonal boron nitride powder on the bonding surface with ball number 7 in the aforementioned inclined rolling ball adhesion test is similar to its spreadability and affinity on human skin. Therefore, the hexagonal boron nitride powder with a high coating area ratio on the bonding surface, especially when applied to human skin, demonstrates excellent spreadability and fineness. This hexagonal boron nitride powder is suitable for use as a raw material in cosmetics. The ratio of oxygen content to specific surface area (N) obtained through nitrogen adsorption in the hexagonal boron nitride powder can reach 0.1 g / 100m³. 2 ]the following.
[0012] The specific surface area (H) of the hexagonal boron nitride powder obtained by water vapor adsorption is 0.8 [m]. 2 Below [g]. This hexagonal boron nitride powder has difficulty absorbing moisture from the atmosphere, thus further inhibiting agglomeration and exhibiting superior ductility.
[0013] The ratio of the specific surface area (H) obtained by water vapor adsorption to the specific surface area (N) obtained by nitrogen adsorption can be below 0.2. This hexagonal boron nitride powder can effectively suppress moisture adsorption, thus further inhibiting agglomeration and exhibiting superior ductility.
[0014] The oxygen content of the aforementioned hexagonal boron nitride powder can be below 0.15% by mass. In this way, the adsorption of water vapor is further suppressed, which can further improve ductility.
[0015] The aforementioned hexagonal boron nitride powder can be used as a raw material in cosmetics. This hexagonal boron nitride powder exhibits excellent ductility, making it suitable for use as a raw material in cosmetics.
[0016] One aspect of this disclosure relates to a cosmetic comprising any of the aforementioned hexagonal boron nitride powders. These hexagonal boron nitride powders inhibit agglomeration and exhibit excellent spreadability. Therefore, cosmetics comprising such hexagonal boron nitride powders will have excellent spreadability.
[0017] The aforementioned hexagonal boron nitride powder exhibits excellent spreadability and fineness when applied to human skin. Therefore, cosmetics containing this hexagonal boron nitride powder also exhibit excellent spreadability and fineness when applied to human skin.
[0018] One aspect of this disclosure relates to a method for manufacturing hexagonal boron nitride powder, comprising: a calcination step of calcining a mixed powder containing hexagonal boron nitride and an additive in a gaseous environment of an inactive gas, ammonia, or a mixture thereof at a temperature of 1600°C or higher and less than 1900°C to obtain a calcined product containing hexagonal boron nitride with a higher crystallinity than that of the hexagonal boron nitride in the mixed powder; a refining step of pulverizing, washing, and drying the calcined product to obtain a dried powder; and an annealing step of annealing the dried powder in a gaseous environment of an inactive gas, ammonia, or a mixture thereof at a temperature of 1900°C or higher.
[0019] In the above manufacturing method, by using additives and calcining at a temperature above 1600°C and below 1900°C, a calcined product containing highly crystalline hexagonal boron nitride can be obtained. After pulverizing the calcined product, washing reduces residual additives, thereby inhibiting particle growth during subsequent annealing. Then, after drying, the calcined product containing crystallized hexagonal boron nitride is annealed at a temperature above 1900°C, thus inhibiting primary particle growth and dispersing oxygen and oxygen-containing functional groups attached to the particle surface, reducing oxygen content. This hexagonal boron nitride powder has a low oxygen content per unit surface area, making it difficult for moisture to adsorb onto the particle surface. It also reduces surface static electricity. It is speculated that for these reasons, the aggregation of hexagonal boron nitride powder is suppressed, resulting in a powder with excellent ductility and fineness. This hexagonal boron nitride powder is suitable as a raw material for cosmetics.
[0020] In the above manufacturing method, prior to the calcination step, a pre-calcination step may be included, in which raw material powders containing boron-containing compound powder and nitrogen-containing compound powder are calcined in an inert gas, ammonia, or a mixture thereof at 600–1300°C to obtain a pre-calcined material containing hexagonal boron nitride with low crystallinity. Furthermore, the mixed powder in the calcination step may also include the pre-calcined material and additives. In this way, by performing pre-calcination at a temperature lower than that of the calcination step, hexagonal boron nitride powder with a high specific surface area can be obtained. Additionally, by performing pre-calcination at a temperature lower than that of the calcination step, hexagonal boron nitride powder with superior ductility and fineness can be obtained.
[0021] The hexagonal boron nitride powder obtained through the above annealing process has an oxygen content relative to the specific surface area (N) obtained by nitrogen adsorption of 0.1 g / 100m³. 2 ]the following.
[0022] The hexagonal boron nitride powder obtained by the above manufacturing method, in the inclined rolling ball adhesion test with an inclined plate having an inclination angle of 30 degrees as specified in JIS Z 0237:2009, on the bonding surface with ball number 7, when spread from one end of the bonding surface to the other using a coating plate at a speed of 1 cm / s, the coating area ratio of the bonding surface can be 77% or more. Here, the coating area ratio is the ratio of the coating area to the total area of the central region of the bonding surface when 0.1 g of hexagonal boron nitride powder is spread on the bonding surface. The central region is a square area with a side length of 10 mm, located 10 mm away from one end of the bonding surface. All of the hexagonal boron nitride powder is disposed on one end of the bonding surface, and between imaginary extensions of a set of opposite sides that define the central region and follow the direction of the application of the hexagonal boron nitride powder.
[0023] In the aforementioned inclined rolling ball adhesion test, the hexagonal boron nitride powder exhibited similar properties on the bonding surface (ball number 7) to its spreadability and affinity on human skin. Therefore, hexagonal boron nitride powder with a high coating area ratio on the aforementioned bonding surface demonstrates excellent spreadability and fineness, particularly when applied to human skin. This hexagonal boron nitride powder is suitable for use as a raw material in cosmetics.
[0024] One aspect of this disclosure relates to a method for manufacturing cosmetics that uses hexagonal boron nitride powder obtained by any of the aforementioned manufacturing methods as a raw material. The hexagonal boron nitride powder obtained by these methods exhibits suppressed agglomeration and excellent spreadability. Therefore, cosmetics manufactured using this hexagonal boron nitride powder as a raw material will possess excellent spreadability.
[0025] One aspect of this disclosure relates to a quality evaluation method comprising the following steps: applying hexagonal boron nitride powder or a powdered composition containing thereto to an adhesive surface using a coating plate; and evaluating the quality based on the coating area of the hexagonal boron nitride powder or the powdered composition containing thereto on the adhesive surface. According to this quality evaluation method, the ductility and fineness of the hexagonal boron nitride powder can be easily evaluated.
[0026] The aforementioned bonding surface can be formed by one side of the carbon tape. Since the carbon tape is black, the coverage area ratio of white hexagonal boron nitride powder on the bonding surface can be determined with high precision. Therefore, the quality evaluation of the hexagonal boron nitride powder can be performed with high precision.
[0027] The aforementioned adhesive surface can be the adhesive surface with ball numbers 6 to 8 in the inclined rolling ball adhesion test with an inclined plate having an inclination angle of 30 degrees, as specified in JIS Z 0237:2009. The spreadability and affinity of hexagonal boron nitride powder on this adhesive surface are similar to those on human skin. Therefore, it is useful as a means of evaluating the spreadability and fineness of cosmetics and their raw materials applied to human skin.
[0028] [Invention Effects]
[0029] One aspect of this disclosure provides a hexagonal boron nitride powder and a method for manufacturing the same, which can produce cosmetics with excellent spreadability. Furthermore, by using the aforementioned hexagonal boron nitride powder, cosmetics with excellent spreadability and a method for manufacturing the same can be provided.
[0030] Another aspect of this disclosure provides a hexagonal boron nitride powder with excellent ductility and fineness, and a method for manufacturing the same. Cosmetics with excellent ductility and fineness can also be provided. Furthermore, a quality evaluation method can be provided to easily evaluate the quality of the hexagonal boron nitride powder. Attached Figure Description
[0031] Figure 1 This is a top view of a quality evaluation apparatus used in an example of a quality evaluation method.
[0032] Figure 2 for Figure 1 Side view of the quality evaluation device.
[0033] Figure 3 This diagram shows the measuring apparatus used to perform an inclined rolling ball viscosity test.
[0034] Figure 4 This photograph illustrates the state of the adhesive surface after hexagonal boron nitride powder was spread on it, as shown in Example 1 and Comparative Example 1. Detailed Implementation
[0035] The following describes embodiments of this disclosure. However, the following embodiments are merely illustrative examples of this disclosure and are not intended to limit this disclosure to the following content.
[0036] In this embodiment, the oxygen content in the hexagonal boron nitride powder is 0.1 g / 100m³ relative to the specific surface area (N) obtained by nitrogen adsorption. 2 The ratio can be less than 0.08 g / 100m³. 2 It can be less than 0.05 g / 100m³. 2 [, or can be less than 0.03 g / 100m] 2 By reducing this ratio, ductility can be improved. This ratio could be, for example, 0.001 g / 100m³. 2 The value above, or possibly 0.005 g / 100m³, may be 0.005 g / 100m³. 2 The above. In this way, good dispersibility in polar solvents can be achieved. Therefore, for example, when using hexagonal boron nitride powder as a raw material in cosmetics, the manufacture of cosmetics can be carried out smoothly. An example range of this ratio is 0.001 to 0.1 g / 100 mg. 2 ].
[0037] The specific surface area (N) obtained by nitrogen adsorption is the value measured using a commercially available specific surface area measuring device, with the adsorbed gas identified as nitrogen. The specific surface area (N) can be 0.5 [m²]. 2 / g] or more, or possibly 1[m 2 / g] or more. By having a high specific surface area (N), the primary particles can be sufficiently reduced in size. In this way, adhesion to skin and wrinkles can be improved. The specific surface area (N) can be 8 [m²]. 2 / g] or less, or possibly 6[m 2 Below [g]. In this way, not only ductility but also smoothness can be significantly improved. Examples of specific surface area (N) ranges from 0.5 to 8 [m²]. 2 / g).
[0038] The oxygen content can be less than 0.15% by mass, or less than 0.12% by mass. Reducing the oxygen content inhibits moisture adsorption on the particle surface. It also reduces static electricity generated on the particle surface. For these reasons, agglomeration of hexagonal boron nitride powder can be suppressed. The oxygen content can be 0.005% by mass or more, or 0.01% by mass or more. In this way, good dispersibility in polar solvents is achieved. Therefore, for example, when using hexagonal boron nitride powder as a raw material in cosmetics, cosmetic manufacturing can proceed smoothly. The oxygen content can be adjusted by changing the calcination temperature and time in the calcination process, and the annealing temperature and time in the annealing process. An example of an oxygen content range is 0.005 to 0.15% by mass.
[0039] The specific surface area (H) obtained through water vapor adsorption is a value measured using a commercially available specific surface area measuring device, with the adsorbed gas identified as water. That is, a larger value indicates a larger amount of water adsorbed on the particle surface. The specific surface area (H) can be 0.8 [m²]. 2 Below / g], or possibly 0.6[m] 2 Below [g]. By having a low specific surface area (H), moisture adsorption on the particle surface can be suppressed, and the aggregation of hexagonal boron nitride powder is inhibited. The specific surface area (H) can be 0.1 [m]. 2 / g] or more, or possibly 0.2[m] 2 [g] or higher. This method ensures good dispersibility in aqueous solvents. An example of a specific surface area (H) range is 0.1 to 0.8 [m²]. 2 / g).
[0040] The ratio of the specific surface area (H) obtained by water vapor adsorption to the specific surface area (N) obtained by nitrogen adsorption can be 0.2 or less, or 0.17 or less. Reducing this ratio further suppresses water adsorption. The lower limit of this ratio can be 0.01 or 0.03. This ensures good dispersibility in polar solvents. An example range for the ratio of specific surface area (H) to specific surface area (N) is 0.01 to 0.2. The ratio of specific surface area (H) to specific surface area (N) can be adjusted by changing the annealing process time. For example, simply increasing the annealing process time reduces the ratio of specific surface area (H) to specific surface area (N).
[0041] The hexagonal boron nitride powder described in this embodiment exhibits excellent spreadability due to its resistance to agglomeration, making it suitable as a raw material for cosmetics. That is, this disclosure also provides a method of using hexagonal boron nitride powder as a raw material in cosmetics. Cosmetics with excellent spreadability can cover a wide area of skin when applied. The coating area ratio of this hexagonal boron nitride powder, as determined by the following quality evaluation method, can be 80% or more, or 90% or more. An example of a coating area ratio range is 80% to 99%.
[0042] One embodiment of the quality evaluation method includes: a first step of applying hexagonal boron nitride powder or a powder composition containing the same onto an adhesive surface using a coating plate; and a second step of determining the coating area ratio of the hexagonal boron nitride powder on the adhesive surface.
[0043] The adhesive surface can be formed by one side of the tape. For example, if the adhesive surface is formed by one side of the carbon tape, the adhesive surface will be black, and the coating area ratio of white hexagonal boron nitride powder or powder composition can be determined with high precision.
[0044] Figure 1 This is a top view of a quality evaluation device used in an example of the aforementioned quality evaluation method. Figure 2 for Figure 1 A side view of the quality evaluation device. The quality evaluation device 100 includes: a base 30 and an adhesive tape 21 attached to the upper surface 30a of the base 30 and having an adhesive surface 21a; a powdered sample 20 disposed on one end 21A of the adhesive tape 21 (adhesive surface 21a); and a coating plate 22 for spreading the sample 20 from one end 21A of the adhesive surface 21a toward the other end 21B.
[0045] The stand 30 can be used without particular restrictions as long as it has a flat upper surface 30a. The coating plate 22 only needs to be rigid enough to prevent deformation when the sample 20 is spread. The stand 30 and the coating plate 22 can be made of resin or metal. The sample 20 can be hexagonal boron nitride powder or a powdered composition containing hexagonal boron nitride powder (e.g., cosmetics).
[0046] The adhesive surface 21a of the tape 21 has a central region 40 in its central portion. The central region 40 is located in the center of the tape 21 (adhesive surface 21a) in a direction opposite to a pair of sides 21C. The central region 40 is a square with sides of length M, divided by four sides. A gap 24 exists between the central region 40 and one end 21A of the adhesive surface 21a. If the coating area ratio is calculated within this central region 40, the variation in the measured value of the coating area ratio is small, allowing for high-precision evaluation of the quality of the sample 20. Based on this quality evaluation device 100 and quality evaluation method, qualities such as the extensibility and fineness of the sample 20 can be evaluated.
[0047] In the first step, a sample 20 is placed at one end 21A of the adhesive surface 21a. At this point, it is sufficient to ensure that a portion of the sample 20 is not adhered to the adhesive surface 21a. Next, the coating plate 22 is oriented towards... Figure 1 and Figure 2 Moving in the direction of the arrow, the sample 20 is spread onto the adhesive surface 21a. The sample 20 adheres to the adhesive surface 21a and is simultaneously supplied to the central region 40 through the gap 24. After the coating plate 22 passes over the central region 40, the first step is complete. The coating plate 22 can move while tilted at a predetermined angle relative to the adhesive surface 21a. The angle (tilt angle θ1) between the coating plate 22 and the adhesive surface 21a is preferably the angle at which the coating plate 22 tilts towards the other end 21B. For example... Figure 2 The tilt angle θ1 can be 40–80 degrees or 50–70 degrees. The moving speed of the coating plate 22 can be 0.1–10 cm / second or 0.5–5 cm / second.
[0048] In the second step, for example, the ratio of the coated area of sample 20 in the central region 40 to the total area of the central region 40 is determined. The quality can be evaluated by the ratio of the coated area. The coated area ratio can be, for example, 80% or more, or 90% or more. The coated area of sample 20 in the central region 40 can be obtained by image analysis of the central region 40. Alternatively, the specific ratio can be waived, and the coating area can be visually compared for relative evaluation.
[0049] According to the quality evaluation method of this embodiment, the quality of hexagonal boron nitride powder or powdered compositions such as cosmetics containing it can be easily evaluated. Even for qualities such as extensibility and fineness, which are general evaluation items for cosmetics and their raw materials but are difficult to standardize, evaluation can be performed easily and with high precision.
[0050] The position and size of the central region 40 and the interval 24, as well as the quantity of the sample 20, can be set according to the quantity and quality of the sample 20 obtained. Additionally, the entire sample 20 can be positioned on one end 21A of the adhesive surface 21a, between imaginary extension lines VL1 and VL2 (see reference). Figure 1 Here, the imaginary extension lines VL1 and VL2 are a set of straight lines extending towards the sample 20 from opposite sides, marking the central region 40 and following the direction in which the hexagonal boron nitride powder is applied. The side length M of the central region 40 can be, for example, 1–50 mm, or 5–20 mm.
[0051] The length L of the adhesive surface 21a (tape 21) can be 5–200 mm or 10–100 mm. The length M of one side of the adhesive surface 21a (tape 21) can be 5–100 mm or 10–50 mm. The width of the coating plate 22 can be greater than the length M.
[0052] The ball number obtained from the inclined rolling ball adhesion test (inclination angle θ1: 30 degrees) of the adhesive surface 21a according to JIS Z 0237:2009 can be 6 to 8. By using such an adhesive surface 21a for quality evaluation, the sensory evaluation of the spreadability and fineness when applied to human skin is more consistent with the evaluation method of this embodiment, enabling high-precision evaluation of the spreadability and fineness of the hexagonal boron nitride powder in cosmetics and its raw materials. From this perspective, the ball number can also be 7.
[0053] Figure 3 This is a diagram showing the measuring apparatus used to perform the inclined rolling ball viscosity test as specified in JIS Z 0237:2009. Figure 3 The measuring device 200 includes: an inclined plate 11 inclined at an angle θ2 (θ2 = 30 degrees) relative to a horizontal plane, a support plate 16 supporting the inclined plate 11, and a fixing part 14 fixing the ball 10 to the upper end of the inclined plate 11. On the inclined plate 11, starting from the fixing part 14 side, a running track 12 and an adhesive tape 21 having an adhesive surface 21a are arranged adjacent to each other in sequence.
[0054] Prepare balls 10 of various sizes, remove the fixing part 14, and let the balls 10 roll down onto the adhesive surface 21a for measurement. Then, among the balls 10 that remain on the adhesive surface 21a for more than 5 seconds, find the ball with the largest size. Change the tape 21 and perform this measurement 3 times, and calculate the average value of the ball numbers corresponding to the largest size. Define this average value as the ball number in this disclosure. The length L0 of the runway 12 and the length L1 of the adhesive surface 21a are both 100 mm.
[0055] In one embodiment, the hexagonal boron nitride powder involved in the inclined ball adhesion test, when applied to the bonding surface 21a with ball number 7 using a coating plate 22 at a speed of 1 cm / s from one end 21A to the other end 21B of the bonding surface 21a, has a coating area ratio of 80% or more. This coating area ratio can be 90% or more. However, the coating area ratio is the ratio of the coating area to the total area of the central region 40 of the bonding surface 21a when 0.1 g of the sample 20 (hexagonal boron nitride powder) is applied to the bonding surface 21a. The entire 0.1 g of the sample 20 is arranged between imaginary extensions VL1 and VL2 that define the central region 40 and run along the direction of applying the sample 20.
[0056] Inclined rolling ball viscosity test, such as Figure 3 As described above, the test is as specified in JIS Z 0237:2009. In this embodiment, the central region 40 is a square region with a side length of 10 mm. Furthermore, Figure 1 The central region 40 is 10 mm away from one end 21A of the adhesive surface 21a. That is, Figure 1 The length G of the interval 24 is 10mm, and the side length M of the central region 40 is 10mm.
[0057] The aforementioned hexagonal boron nitride powder exhibits excellent spreadability and fineness due to its high coating area ratio on the bonding surface 21a. Furthermore, the spreadability and affinity of the hexagonal boron nitride powder on bonding surface 21a (ball number 7) in the aforementioned inclined rolling ball adhesion test are similar to those on human skin. Therefore, the hexagonal boron nitride powder with a high coating area ratio on bonding surface 21a, especially when applied to human skin, demonstrates excellent spreadability and fineness. This hexagonal boron nitride powder is suitable for use as a raw material in cosmetics.
[0058] This disclosure also provides a method of using hexagonal boron nitride as a raw material in cosmetics. The cosmetic, possessing excellent spreadability, can cover a wide area of skin when applied.
[0059] For hexagonal boron nitride powder with a coating area ratio of 80% or higher, the specific surface area (N), oxygen content, oxygen content to specific surface area (N), specific surface area (H), and specific surface area (H) to specific surface area (N) should all fall within the aforementioned numerical ranges. This method not only improves ductility and fineness but also significantly enhances smoothness.
[0060] One embodiment of the cosmetic involves a product containing any of the aforementioned hexagonal boron nitride powders. This hexagonal boron nitride powder exhibits suppressed moisture adsorption on its particle surface and also suppresses surface static electricity. Therefore, it is believed that the hexagonal boron nitride powder becomes less prone to agglomeration. Consequently, cosmetics containing this hexagonal boron nitride powder exhibit excellent spreadability.
[0061] Cosmetics include, for example, foundations (powder foundations, liquid foundations, cream foundations), loose powders, highlighting makeup, eyeshadows, eyeliners, nail polishes, lipsticks, blushes, and mascaras. Among these cosmetics, hexagonal boron nitride powder is particularly suitable for foundations and eyeshadows. The content of hexagonal boron nitride powder in cosmetics is, for example, 0.1% to 70% by mass. Cosmetics can be manufactured by well-known methods. Methods for manufacturing cosmetics include, for example, the process of blending hexagonal boron nitride powder with other raw materials.
[0062] One embodiment of the method for manufacturing hexagonal boron nitride powder includes: a pre-calcination step of calcining a raw material powder containing a boron-containing compound powder and a nitrogen-containing compound powder in an inert gas environment, an ammonia environment, or a mixture thereof at 600–1300°C to obtain a pre-calcined material containing at least one of the group consisting of low-crystallinity hexagonal boron nitride and amorphous hexagonal boron nitride; a calcination step of calcining a mixed powder containing the pre-calcined material and an additive in an inert gas and / or ammonia environment at a temperature of 1600°C or higher and less than 1900°C to obtain a calcined material; a refining step of pulverizing, washing, and drying the calcined material to obtain a dried powder; and an annealing step of annealing the dried powder in an inert gas, ammonia, or a mixture thereof at a temperature of 1900°C or higher.
[0063] Boron-containing compounds include boric acid, boron oxide, and borax. Nitrogen-containing compounds include dicyandiamine, melamine, and urea. In the raw material powder containing both boron-containing and nitrogen-containing compounds, the molar ratio of boron atoms to nitrogen atoms can be 2:8 to 8:2, or 3:7 to 7:3. The raw material powder may also contain components other than the above-mentioned compounds. For example, it may contain carbonates such as lithium carbonate and sodium carbonate as pre-calcination aids. It may also contain reducing substances such as carbon.
[0064] The raw material powder containing the above-mentioned components is pre-fired, for example, in an electric furnace, in an inert gas environment such as nitrogen, helium, or argon, an ammonia environment, or a mixed gas environment composed of these. The pre-fired temperature can be 600–1300°C, or 800–1200°C, or 900–1100°C. The pre-fired time can be, for example, 0.5–5 hours, or 1–4 hours.
[0065] The pre-calcined product obtained by pre-calcination includes at least one selected from the group consisting of low-crystallinity hexagonal boron nitride and amorphous hexagonal boron nitride. The pre-calcination process involves reacting the boron nitride at a temperature lower than that of the calcination process described later. By lowering the pre-calcination temperature, particle growth can be suppressed, thereby reducing the particle size of the final obtained boron nitride powder. Furthermore, the specific surface area (N) of the hexagonal boron nitride powder can be increased.
[0066] Next, the obtained pre-calcined material is mixed with additives to obtain a mixed powder. Examples of additives include borates such as sodium borate, and carbonates such as sodium carbonate, calcium carbonate, and lithium carbonate. The amount of additive added can be 2 to 20 parts by mass, or 2 to 8 parts by mass, relative to 100 parts by mass of the pre-calcined material containing hexagonal boron nitride. This mixed powder is then calcined, for example, in an electric furnace, in an inert gas environment such as nitrogen, helium, or argon, in an ammonia environment, or in a mixed gas environment containing these gases.
[0067] During the calcination process, boron nitride is formed and crystallized in the presence of additives. This improves the crystallinity of the boron nitride in the pre-calcined material. The calcination temperature is above 1600℃ and below 1900℃. This calcination temperature can be 1650–1850℃, or 1650–1750℃. The calcination time can be, for example, 0.5–5 hours, or 1–4 hours.
[0068] Lowering the calcination temperature can increase the specific surface area (N) and specific surface area (H). However, if the calcination temperature is too low, there is a tendency for insufficient formation and crystallization of hexagonal boron nitride. Insufficient crystallization of hexagonal boron nitride can lead to reduced smoothness when used in cosmetics. The same tendency also occurs with excessively short calcination times. On the other hand, increasing the calcination temperature will decrease the specific surface area (N) and specific surface area (H). If the calcination temperature is too high, the crystal growth of hexagonal boron nitride will be excessive, making it difficult to micronize. The same tendency also occurs with excessively long calcination times.
[0069] The calcined product obtained from the calcination process can be pulverized using conventional pulverizing equipment. The pulverized product contains impurities in addition to hexagonal boron nitride. Examples of impurities include residual additives and water-soluble boron compounds. These impurities are reduced during the refining process by washing. After washing, solid-liquid separation and drying are performed to obtain a dry powder. Washing solutions used include water, aqueous solutions containing acidic substances, organic solvents, and mixtures of organic solvents and water. From the viewpoint of avoiding the re-introduction of impurities, water with a conductivity of less than 1 mS / m is preferable. Examples of acidic substances include inorganic acids such as hydrochloric acid and nitric acid. Examples of organic solvents include water-soluble organic solvents such as methanol, ethanol, propanol, isopropanol, and acetone. There are no particular limitations on the washing method; for example, the pulverized product can be washed by immersing it in the washing solution and stirring, or by spraying the product with the washing solution.
[0070] After cleaning, the cleaning solution can be separated into solid and liquid components using methods such as decanting, vacuum filtration, pressure filtration, rotary filtration, sedimentation separators, or combinations thereof. The separated solid components are then dried using a conventional dryer to obtain a dry powder. Examples of dryers include rack dryers, fluidized bed dryers, spray dryers, rotary dryers, conveyor belt dryers, and combinations thereof. After drying, coarse particles can be removed, for example, by using sieves for grading.
[0071] In the annealing process, the dry powder is heated to 1900°C or higher in an inert gas environment such as nitrogen, helium, or argon, an ammonia environment, or a mixture of these gases, using an electric furnace, for example. This annealing temperature, from the viewpoint of sufficiently reducing oxygen content, can be 1950°C or higher, or even 2000°C or higher. By performing the annealing process, oxygen present on the particle surface in the form of functional groups, etc., can be dispersed, thereby reducing the oxygen content. In the annealing process, since the dry powder, whose additives have been reduced more significantly than those in the calcined product through the refining process, is annealed, particle growth can be suppressed, and the oxygen content can be reduced simultaneously.
[0072] From the perspective of suppressing particle growth, the annealing temperature can be below 2200℃ or below 2100℃. The annealing time, from the perspective of sufficiently reducing oxygen content while suppressing particle growth, can be, for example, 0.5 to 5 hours or 1 to 4 hours.
[0073] In this way, the aforementioned hexagonal boron nitride powder can be obtained. The description of the embodiment of the hexagonal boron nitride powder can be applied to the above manufacturing method. One example of the hexagonal boron nitride powder obtained by the above manufacturing method is that, in an inclined rolling ball adhesion test, when the coating plate 22 is used to spread the coating on the bonding surface 21a (ball number 7) at a speed of 1 cm / s from one end 21A to the other end 21B of the bonding surface 21a, the coating area ratio of the bonding surface 21a is 80% or more.
[0074] The method for manufacturing hexagonal boron nitride powder is not limited to the embodiments described above. For example, the annealing process can be repeated multiple times. In addition, after the annealing process, a pyrolysis process can be performed to pyrolyze the hexagonal boron nitride powder using a homogenizer or the like that that generates ultrasonic vibration.
[0075] The above description describes several embodiments of this disclosure; however, this disclosure is not limited to the above embodiments at all.
[0076] [Example]
[0077] The contents of this disclosure will be described in more detail with reference to the embodiments and comparative examples, but this disclosure is not limited to the following embodiments.
[0078] (Example 1)
[0079] [Preparation of Hexagonal Boron Nitride Powder]
[0080] <Pre-firing process>
[0081] 100.0 g of boric acid powder (purity ≥ 99.8% by mass, manufactured by Kanto Chemical Co., Ltd.) and 90.0 g of melamine powder (purity ≥ 99.0% by mass, manufactured by Wako Pure Chemical Co., Ltd.) were mixed in an alumina mortar for 10 minutes to obtain a mixed raw material. The dried mixed raw material was placed in a container made of hexagonal boron nitride and placed in an electric furnace. Nitrogen gas was circulated in the electric furnace while the temperature was increased from room temperature to 1000°C at a rate of 10°C / min. After maintaining the temperature at 1000°C for 2 hours, heating was stopped and the mixture was allowed to cool naturally. The electric furnace was turned on when the temperature dropped below 100°C. In this way, a pre-calcined product containing low-crystallinity hexagonal boron nitride was obtained.
[0082] <Calcination Process>
[0083] Add 3.0g of sodium carbonate (purity ≥ 99.5% by mass) as an auxiliary agent to 100.0g of pre-calcined material, and mix for 10 minutes using an alumina mortar. Place the mixture in the aforementioned electric furnace. Allow nitrogen gas to circulate within the furnace while simultaneously raising the temperature from room temperature to 1700°C at a rate of 10°C / min. After maintaining the calcination temperature at 1700°C for 4 hours, stop heating and allow it to cool naturally. Turn on the furnace when the temperature drops below 100°C. Recover the resulting calcined material and pulverize it for 3 minutes using an alumina mortar to obtain coarse hexagonal boron nitride powder.
[0084] <Refining Process>
[0085] To remove impurities from the coarse hexagonal boron nitride powder, 30g of the powder was added to 500g of dilute nitric acid (nitric acid concentration: 5% by mass), and stirred at room temperature for 60 minutes. After stirring, solid-liquid separation was achieved by vacuum filtration, and the powder was washed with water (conductivity: 1 mS / m) until the filtrate became neutral. After washing, the powder was dried at 120°C for 3 hours using a dryer to obtain a dry powder.
[0086] <Annealing process>
[0087] The dried powder was placed in the aforementioned electric furnace. Nitrogen gas was circulated within the furnace while the temperature was increased from room temperature to 2000°C at a rate of 10°C / min. After maintaining the temperature at 2000°C for 4 hours, heating was stopped, and the powder was allowed to cool naturally. The furnace was then turned on when the temperature dropped below 100°C. The resulting calcined material was recovered and pulverized for 3 minutes using an alumina mortar. Coarse powder was removed from the dried powder using an ultrasonic vibrating sieve (manufactured by Xinghe Industrial Co., Ltd., trade name: KFS-1000, pore size 250μm) to obtain the hexagonal boron nitride powder of Example 1.
[0088] [Evaluation of Hexagonal Boron Nitride Powder 1]
[0089] <Determination of specific surface area (N)>
[0090] The specific surface area of the hexagonal boron nitride powder prepared in Example 1 was determined using a specific surface area measuring apparatus (manufactured by Yuasa Ionics, apparatus name: MONOSORB) via the BET single-point method. Nitrogen gas was used as the adsorbed gas, and helium gas was used as the carrier gas. A 1g sample was dried and degassed at 300°C for 15 minutes before measurement. The results are shown in Table 2 under "Specific Surface Area (N)".
[0091] <Determination of specific surface area (H)>
[0092] The hexagonal boron nitride powder prepared in Example 1 was degassed under vacuum at 300°C for 12 hours. H₂O was used as the adsorption gas, and the specific surface area (H) of the degassed hexagonal boron nitride powder was determined by the BET method using a commercially available adsorption capacity measuring device (MicrotracBEL, device name: BELSORP-maxII). The measurement results are shown in Table 2 under "Specific Surface Area (H)". The ratio of specific surface area (H) to specific surface area (N) is also disclosed in Table 2.
[0093] <Determination of Oxygen Content>
[0094] Oxygen content was determined using a simultaneous oxygen / nitrogen analyzer (Horiba Manufacturing Co., Ltd., device name: EMGA-920). Specifically, hexagonal boron nitride powder was heated from room temperature to 3000°C in a helium atmosphere at a heating rate of 4.6°C / second, while simultaneously measuring the oxygen and nitrogen contents. The oxygen content was then defined as the oxygen content detected during periods when no nitrogen was detected. The measurement results are shown in Table 2. The ratio of oxygen content to specific surface area (N) is also disclosed in Table 2.
[0095] [Evaluation of Hexagonal Boron Nitride Powder 2]
[0096] <Ball number on the adhesive surface>
[0097] Commercially available carbon tape (double-sided adhesive tape for SEM) was prepared as a test piece. The tack of one adhesive side of the carbon tape was determined using the inclined rolling ball tack test specified in JIS Z 0237:2009. Specifically, the following was prepared: Figure 3 The measuring apparatus 200 is shown. The tilt angle θ2 of the tilt plate 11 is set to 30 degrees, and a polyethylene terephthalate film as specified in JIS 2318 is attached to the runway. The length L0 of the runway is set to 100 mm, and the length L1 of the carbon tape 21 (adhesive surface 21a) is set to 100 mm.
[0098] Balls of 31 different sizes and materials, numbered 2 to 32, conforming to JIS Z 0237:2009, were rolled sequentially from the lowest number ball, starting from the initial position. A ball that remained on the adhesive surface 21a for more than 5 seconds was rated "A," while a ball that did not stop on the adhesive surface 21a or whose stopping time was less than 5 seconds was rated "B." Three test pieces (n=3) were used for the test. The results are shown in Table 1.
[0099] [Table 1]
[0100]
[0101] As shown in Table 1, the ball number (average) of adhesive surface 21a is 7. The following evaluation of the coating area ratio was performed using carbon tape with this adhesive surface.
[0102] <Evaluation of Coating Area Ratio>
[0103] like Figure 1 and Figure 2 As shown, the carbon tape 21 is cut to a specified size (width W × length L = 12mm × 50mm), and the adhesive side opposite to the adhesive side 21a (one side of the double-sided tape) of the ball number 7 is attached to the upper surface 30a of the base 30. Figure 1 and Figure 2 As shown, 0.1 g of hexagonal boron nitride powder from Example 1 was placed as sample 20 at one end 21A along the length of the carbon tape 21. Sample 20 was positioned between imaginary extension lines VL1 and VL2. The angle (tilt angle θ1) between the coating plate 22 and the upper surface 30a was maintained at 60 degrees, while along the length of the carbon tape 21 ( Figure 1 and Figure 2 (in the direction of the arrow), move the coating plate 22 at a speed of 1 cm / s to spread the hexagonal boron nitride powder on the bonding surface 21a.
[0104] Figure 4 This photo shows the state of the carbon tape after hexagonal boron nitride powder has been spread on the bonding surface. Figure 4 The photograph shown in Figure A illustrates the state of the adhesive surface after the hexagonal boron nitride powder of Example 1 has been spread. (The text then abruptly shifts to a different topic: obtaining...) Figure 1 The coating area ratio in the central region 40 of the adhesive surface 21a is shown. This central region 40 is a square region with a side length of 10 mm, located 10 mm from one end 21A and 1 mm from each of the two sides 21C. The ratio of the coating area of the hexagonal boron nitride powder to the total area of the central region 40 was determined using commercially available image analysis software (WinROOF). Examples of coating area ratios are shown in Table 3.
[0105] [Evaluation of Hexagonal Boron Nitride Powder 3]
[0106] <Evaluation of Extensibility and Detail>
[0107] 0.2g of hexagonal boron nitride powder from Example 1 was placed on one end of an artificial skin (manufactured by Idemitsu Technofin Co., Ltd., trade name: SUPPLALE PBZ13001 BK, length × width = 10mm × 50mm). The hexagonal boron nitride powder was spread longitudinally using a spatula, ensuring it was applied to the surface of the artificial skin. Image analysis was performed using commercially available image analysis software (WinROOF) to determine the ratio of the hexagonal boron nitride powder coverage area to the total area of the artificial skin. A larger ratio indicates better elasticity. The evaluation criteria for elasticity are based on the coverage area ratio, as shown below.
[0108] Regarding the fineness, the cross-section along the depth direction of the artificial skin after applying and spreading the hexagonal boron nitride powder of Example 1 was observed using a microscope (Keyence Co., Ltd., digital microscope VHX-7000). The proportion (number basis) of wrinkles in the artificial skin with hexagonal boron nitride powder (BN) embedded was then calculated. The evaluation criteria for fineness are described below. The evaluation results for elasticity and fineness are shown in Tables 2 and 3. Furthermore, the evaluation results for elasticity are disclosed in both Tables 2 and 3.
[0109] [Evaluation Criteria for Extensibility]
[0110] • Excellent: Coverage area ratio is over 95%
[0111] • Good: Coverage area is above 80% but less than 95%
[0112] • Slightly good: Coverage area is above 70% but less than 80%
[0113] • Standard: Coverage area is 60% or more but less than 70%
[0114] • Poor: Coverage area ratio is above 40% but less than 60%.
[0115] • Very poor: Coverage area less than 40%
[0116] [Evaluation Criteria for Detail]
[0117] • Excellent: Over 85% of wrinkles treated with BN are covered.
[0118] • Good: The proportion of wrinkles with BN penetration is above 80% and less than 85%.
[0119] • Slightly good: The proportion of wrinkles with BN penetration is above 70% but less than 80%.
[0120] • Normal: The proportion of wrinkles with BN penetration is higher than 55% but less than 70%.
[0121] • Not good: The proportion of wrinkles with BN penetration is less than 55%.
[0122] (Example 2)
[0123] Except for changing the calcination temperature to 1600℃, hexagonal boron nitride powder was prepared in the same manner as in Example 1. Then, the various measurements and evaluations of the hexagonal boron nitride powder were performed in the same manner as in Example 1. The results are shown in Tables 2 and 3.
[0124] (Example 3)
[0125] Except for changing the holding time at 2000°C in the annealing process to 2 hours, hexagonal boron nitride powder was prepared in the same manner as in Example 1. Then, the various measurements and evaluations of the hexagonal boron nitride powder were performed in the same manner as in Example 1. The results are shown in Tables 2 and 3.
[0126] (Example 4)
[0127] Except for the addition of 3.0 g of sodium carbonate (purity ≥ 99.5% by mass) as an auxiliary agent to the dried mixed raw materials, and the calcination process performed instead of a pre-calcination process, hexagonal boron nitride powder was produced in the same manner as in Example 1. Then, various measurements and evaluations of the hexagonal boron nitride powder were performed in the same manner as in Example 1. The results are shown in Tables 2 and 3.
[0128] (Comparative Example 1)
[0129] Without performing an annealing process, coarse particles were removed in the refining process, and the resulting powder was designated as hexagonal boron nitride powder of Comparative Example 1. Similar to Example 1, various measurements and evaluations of the hexagonal boron nitride powder were performed. The results are shown in Tables 2 and 3. Figure 4 The photograph shown in the image is of the state after the hexagonal boron nitride powder of Comparative Example 1 has been spread on the adhesive surface 21a.
[0130] [Table 2]
[0131]
[0132] As shown in Table 2, it was confirmed that compared with Comparative Example 1, Examples 1-3 had lower oxygen content per unit specific surface area (N) and a smaller ratio of specific surface area (H) to specific surface area (N). The evaluation results of Examples 1 and 3 confirmed that shortening the annealing process time increased the ratio of specific surface area (H) to specific surface area (N). Observing the appearance, Comparative Example 1 showed the formation of agglomerated lumps, while Examples 1-4 showed significantly fewer agglomerated lumps compared to Comparative Example 1. Therefore, it is speculated that Examples 1-4 have superior ductility compared to Comparative Example 1. Example 1 exhibited the best ductility with particularly few agglomerated lumps.
[0133] [Table 3]
[0134] Example 1 95 very good very good Example 2 82 good good Example 3 80 good Slightly better Example 4 77 Slightly better Slightly better Comparative Example 1 75 Very bad not good
[0135] As shown in Table 3, it was confirmed that a larger coating area ratio results in easier application, excellent spreadability, and easier penetration into wrinkles and other uneven surfaces, leading to superior fineness. Figure 4 A comparison of tape A and tape B also confirms that, compared with Comparative Example 1, the coating area ratio of Example 1 is larger.
[0136] [Industry availability]
[0137] According to this disclosure, hexagonal boron nitride powder with excellent spreadability and fineness can be provided. Furthermore, cosmetics with excellent spreadability and fineness can be provided by using the aforementioned hexagonal boron nitride powder.
[0138] [Symbol Explanation]
[0139] 10: Ball
[0140] 11: Inclined plate
[0141] 12: Runway
[0142] 14: Fixing part
[0143] 16: Support board
[0144] 20: Sample
[0145] 21: Adhesive tape (carbon tape)
[0146] 21A: One end
[0147] 21B: The other end
[0148] 21C: Side
[0149] 21a: Adhesive surface
[0150] 22: Coated board
[0151] 24: Interval
[0152] 30:pedestal
[0153] 30a: Upper surface
[0154] 40: Central Region
[0155] 100: Quality Evaluation Device
[0156] 200: Measuring device
Claims
1. A hexagonal boron nitride powder, the specific surface area N obtained by nitrogen adsorption is 6 [m²]. 2 Below [g], the ratio of oxygen content to the specific surface area N is 0.1 g / 100m². 2 the following.
2. The hexagonal boron nitride powder as described in claim 1, in the inclined rolling ball adhesion test with an inclined plate having an inclination angle of 30 degrees as specified in JIS Z 0237:2009, when the adhesive surface with ball number 7 is coated with a coating plate at a speed of 1 cm / s from one end of the adhesive surface to the other end, the coating area ratio of the adhesive surface is 77% or more. in, The coating area ratio is the ratio of the coating area to the total area of the central region of the adhesive surface when 0.1g of the hexagonal boron nitride powder is spread on the adhesive surface; the central region is a square area with a side length of 10mm, which is 10mm away from one end of the adhesive surface; all of the hexagonal boron nitride powder is disposed on one end of the adhesive surface, and between a set of imaginary extensions of opposite sides that divide the central region along the direction in which the hexagonal boron nitride powder is spread.
3. The hexagonal boron nitride powder as described in claim 1 or 2, wherein, The specific surface area H obtained through water vapor adsorption is 0.8 m². 2 / g and below.
4. The hexagonal boron nitride powder as described in claim 1 or 2, wherein, The ratio of the specific surface area H obtained by water vapor adsorption to the specific surface area N obtained by nitrogen adsorption is less than 0.
2.
5. The hexagonal boron nitride powder as described in claim 1 or 2, wherein, The oxygen content is below 0.15% by mass.
6. The hexagonal boron nitride powder as described in claim 1 or 2, used as a raw material for cosmetics.
7. A cosmetic product comprising hexagonal boron nitride powder according to any one of claims 1 to 6.
8. A method for manufacturing hexagonal boron nitride powder, comprising the following steps: The calcination process involves calcining a mixed powder containing hexagonal boron nitride and an additive in a gaseous environment of inactive gas, ammonia, or a mixture thereof at a temperature above 1600°C and below 1900°C to obtain a calcined product containing hexagonal boron nitride with higher crystallinity than the hexagonal boron nitride in the mixed powder. The refining process involves pulverizing, washing, and drying the calcined material to obtain a dry powder; and The annealing process involves annealing the dried powder in a gaseous environment of inert gas, ammonia, or a mixture thereof at a temperature above 1900°C. The specific surface area N of the hexagonal boron nitride powder, obtained by nitrogen adsorption, is 6 [m²]. 2 Below [g], the ratio of oxygen content to the specific surface area N is 0.1 g / 100m². 2 the following.
9. The method for manufacturing hexagonal boron nitride powder as described in claim 8, wherein, Prior to the calcination process, the following is included: A pre-calcination process involves calcining raw material powders containing boron-containing compounds and nitrogen-containing compounds at 600–1300°C in an inert gas, ammonia, or a mixture thereof to obtain a pre-calcined material containing hexagonal boron nitride. The mixed powder in the calcination process comprises the pre-calcined material and the additives.
10. The method for manufacturing hexagonal boron nitride powder as described in claim 8 or 9, wherein, The oxygen content of the hexagonal boron nitride powder obtained in the annealing process is 0.1 g / 100m³ relative to the specific surface area N obtained by nitrogen adsorption. 2 the following.
11. The method for manufacturing hexagonal boron nitride powder as described in claim 8 or 9, wherein, In the inclined rolling ball adhesion test with an inclined plate having an inclination angle of 30 degrees as specified in JIS Z 0237:2009, when the hexagonal boron nitride powder is spread from one end of the adhesive surface to the other end of the adhesive surface using a coating plate at a speed of 1 cm / s on the adhesive surface with ball number 7, the coating area ratio of the adhesive surface is more than 77%. Wherein, the coating area ratio is the ratio of the coating area to the total area of the central region of the adhesive surface when 0.1g of the hexagonal boron nitride powder is spread on the adhesive surface; the central region is a square area with a side length of 10mm, which is 10mm away from one end of the adhesive surface; the hexagonal boron nitride powder is entirely disposed on one end of the adhesive surface, and between a set of imaginary extension lines that divide the central region along the direction in which the hexagonal boron nitride powder is spread.
12. A method for manufacturing a cosmetic, using hexagonal boron nitride powder obtained by any one of claims 8 to 11 as a raw material to manufacture the cosmetic.
13. A quality evaluation method for cosmetic raw materials, comprising the following steps: Using a coating plate, apply hexagonal boron nitride powder or a powdered composition containing it to the bonding surfaces, and Quality is evaluated based on the coating area of the hexagonal boron nitride powder or a powdered composition containing it on the adhesive surface. in, The adhesive surface is formed by one side of the carbon tape. Furthermore, the bonding surface is used in the inclined rolling ball adhesion test with an inclined plate having an inclination angle of 30 degrees, as specified in JIS Z 0237:2009, where the ball number is 6 to 8. In the spreading process, a coating plate is used to spread the coating from one end of the adhesive surface to the other end at a speed of 1 cm / second.
Citation Information
Patent Citations
Hexagonal crystal boron nitride powder and cosmetic
JP2019043792A
Manufacture of powdered bn
JP1985033204A
Hexagonal boron nitride powder and its production
JP1993186205A
Boron nitride particles and resin composition
WO2021100816A1